Uncovering Multisensory Processing through Non-Invasive Brain Stimulation - Bolognini, Nadia; Maravita, Angelo (Frontiers in Psychology, 2011)
Most of current knowledge about the mechanisms of multisensory integration of environmental stimuli by the human brain derives from neuroimaging experiments. However, neuroimaging studies do not always provide conclusive evidence about the causal role of a given area for multisensory interactions, since these techniques can mainly derive correlations between brain activations and behaviour. Conversely, techniques of non-invasive brain stimulation (NIBS) represent a unique and powerful approach to inform models of causal relations between specific brain regions and individual cognitive and perceptual functions. Although NIBS have been widely used in cognitive neuroscience, its use in the study of multisensory processing in the human brain appears a quite novel field of research. In this paper, we will review and discuss recent studies that have used two techniques of NIBS, namely Transcranial Magnetic Stimulation (TMS) and Transcranial Direct Current Stimulation (tDCS), for investigating the causal involvement of unisensory and heteromodal cortical areas in multisensory processing, the effects of multisensory cues on cortical excitability in unisensory areas and the putative functional connections among different cortical areas subserving multisensory interactions. The emerging view is that NIBS is an essential tool available to neuroscientists seeking for causal relationships between a given area or networks and multisensory processes. With its already large and fast increasing usage, future work using NIBS in isolation, as well as in conjunction with different neuroimaging techniques, could substantially improve our understanding of multisensory processing in the human brain.